Hydrogen refueling of a fuel cell electric vehicle - Sahin, Habip (Pergamon-Elsevier Science Ltd, 2024)
The rapid development of the transportation sector requires consideration of fossil fuel consumption and its negative effects. For this reason, electric vehicles have started to be an alternative to conventional ones that use fossil fuels. As a transportation fuel, hydrogen can be considered as a suitable alternative to fossil fuels. The durations for hydrogen refueling and fossil fuel refueling in conventional vehicles are close to each other. To promote the use of fuel cell vehicles, it is imperative to build the necessary facilities, including hydrogen fuel stations, that will support this need in the near future. In this study, the refueling of the hydrogen tank is simulated for the use of a fuel cell electric vehicle in real usage conditions and it takes 280 s to supply 4.34 kg of hydrogen to the tank of the vehicle, which is driven with a range of 650 km. The fuel economy of the vehicle is compared with conventional vehicles and was found to be 11.0 cent/km and 10.2 cent/km, respectively. Renewable supported production technologies are taken as a reference in hydrogen pricing, and these costs are even lower in hydrocarbon-based production. Depending on the source of the hydrogen, the emission intensity of the vehicle can be reduced to 4.7 gCO2/km with green hydrogen technologies, while it can be up to 166.8 gCO2/km in case of intensive fossil resource use. This study shows that a fuel cell vehicle can compete with traditional ones in terms of range, refueling time and fuel economy and is more environmentally friendly.
Keywords: Electric vehicle; Driving cycle; Fuel cell; Hydrogen; Lithium-ion battery